2007
DOI: 10.5694/j.1326-5377.2007.tb00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Mycobacterium ulcerans infection with combined surgery and antibiotic therapy: findings from a south‐eastern Australian case series

Abstract: Objective: To describe the effect of antibiotics on outcomes of treatment for Buruli or Bairnsdale ulcer (BU) in patients on the Bellarine Peninsula in south‐eastern Australia. Design: Observational, non‐randomised study with data collected prospectively or through medical record review. Patients and setting: All 40 patients with BU managed by staff of Barwon Health's Geelong Hospital (a public, secondary‐level hospital) between 1 January 1998 and 31 December 2004. Main outcome measures: Epidemiology, clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 18 publications
1
73
1
Order By: Relevance
“…In addition, the complications mainly involved gastrointestinal intolerance with no significant sequelae. This differs from the significant incidence of serious adverse events previously described for alternative antibiotics such as streptomycin [5], [28] and amikacin [6]. It is important to note that the complication rates were higher in our study compared to studies from African populations [4], [5], [7].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, the complications mainly involved gastrointestinal intolerance with no significant sequelae. This differs from the significant incidence of serious adverse events previously described for alternative antibiotics such as streptomycin [5], [28] and amikacin [6]. It is important to note that the complication rates were higher in our study compared to studies from African populations [4], [5], [7].…”
Section: Discussioncontrasting
confidence: 99%
“…One case remained positive after 36 days of antibiotics but still achieved cure, reinforcing findings from previous studies that a small proportion of cases may remain culture positive after 1–2 months of antibiotics but still achieve cure with at least 8 weeks of antibiotics [4], [5]. The proportion of patients receiving antibiotic treatment significantly increased from 2005 as it became apparent in patients treated at Barwon Health that antibiotics were associated with a reduction in disease recurrences and permitted more conservative surgery to be performed [6].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The anatomical location of a M. ulcerans lesion was described as distal if it was on the elbow or below, or on the knee or below [7], [10].…”
Section: Methodsmentioning
confidence: 99%
“…The initial lesion size was also smaller in the placebo group. A retrospective study in Australia found that use of RIF plus ciprofloxacin significantly improved the outcome from surgical treatment [82]. Use of antibiotics alone in four patients was not successful.…”
Section: Antibiotic Treatment For Buruli Ulcer: In Vitro Culture Moumentioning
confidence: 99%